Les rendez-vous manqués de l’ethnologie et de la primatologie de terrain (1960-2010) - Vincent Leblan (Revue de Primatologie)
In ethnology, the study of primate behavior is a marginal study object which allows to demarcate the discipline’s boundaries. This view is supported by the analysis of a few interdisciplinary experiences about primates in France in the past decades. The ambition of a primate societies ethnography presently called for in ethology is then examined under two different angles:for one part, by tracing the unrecognized descent of the use of the culture concept in primatology to American (USA) cultural anthropologists’ comments on anthropoid psychology during the interwar years, while this invention is often traced exclusively to Japanese primatology in the postwar years. For the other part, by comparing how ethnologists and primatologists engage with the beings under study: their field practices seem able to constitute more solid epistemological grounds for bridge-building than the positivist conception of culture elaborated in a period of ethnology’s formation and nowadays borrowed by primatologists. The article finally turns to a decade of “ethnoprimatology”: in the perspective of unifying nature and culture in conservation, field primatology is starting to enroll contemporary human societies in its research agenda. But by dissecting human “local beliefs” in the same way as primate traditions, this applied ecology program neglects the complexity of relationships between societies and environments. To the contrary, the ethnography of hunting practices in Guinea and Guinea-Bissau (Boké region, Tristao Islands) presented here is based on a conception of knowledge as inseparable from its mobilization and transformation through action. This approach avoids reducing culture to a set of beliefs deemed favourable or unfavourable to conservation, isolated from their context, which could be manipulated for the management of primate populations.